Protocolo obstétrico y su relación con los resultados materno-fetales en la atención del parto prematuro, Hospital General IESS Babahoyo, octubre 2024 - mayo 2025. - Ñaupa Chimbo, Katherine Lisette (2025)
Premature birth is the leading cause of neonatal morbidity and mortality on a global scale. This analysis examined the link between observance of the obstetric protocol and maternal-fetal outcomes in premature births attended at the IESS Babahoyo General Hospital during the period between October 2024 and May 2025. The methodology was used in a descriptive and analytical manner, with a quantitative orientation and a cross-sectional design. 87 clinical records of mothers with premature births were examined, evaluating the degree of compliance with obstetric protocols through essential indicators. The findings showed an overall compliance of 91.95%, highlighting the application of antenatal corticosteroids, tocolytics and prophylactic antibiotics. However, failures were detected in interdisciplinary coordination and in the adequate implementation of clinical interventions.